2019
DOI: 10.1177/2473011419889023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Strengthening Opioid Misuse Prevention (STOP) Act on Opioid Prescription Practices After Ankle Fracture Fixation

Abstract: Background: In North Carolina, the Strengthen Opioid Misuse Prevention Act of 2017 (STOP Act) went into effect on January 1, 2018, intending to increase oversight over opioid prescriptions. This study compares postoperative narcotic prescription practices following operative fixation of ankle fractures before and after the STOP Act. Methods: This study was a retrospective review of patients 18 years and older who underwent operative fixation of ankle fractures between January 1 and June 30, 2017 (before STOP A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…Hussaini et al compared outcomes among patients with ankle fractures who underwent treatment before and after the STOP Act enactment and found no significant difference in the percentage of patients who made pain-related phone calls, ED visits, or unplanned clinic visits. 7 Similar findings were observed in the current study, which refutes the notion that increased pain-related concerns could potentially add strain to the health care system. Future studies involving larger cohorts should investigate whether these trends are consistent for enactment of state and institutional policies curbing opioid prescriptions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hussaini et al compared outcomes among patients with ankle fractures who underwent treatment before and after the STOP Act enactment and found no significant difference in the percentage of patients who made pain-related phone calls, ED visits, or unplanned clinic visits. 7 Similar findings were observed in the current study, which refutes the notion that increased pain-related concerns could potentially add strain to the health care system. Future studies involving larger cohorts should investigate whether these trends are consistent for enactment of state and institutional policies curbing opioid prescriptions.…”
Section: Discussionsupporting
confidence: 90%
“…Aran et al demonstrated a clinically significant decline in opioid prescriptions within their orthopedic department under the STOP Act, while a study led by Hussaini et al concluded that such a reduction can be done without increased strain on health care resources. 6,7 There remains, however, very limited evidence on the effect of prescription opioid control reform on patient functional outcomes and pain after spine surgery. As such, the purpose of this study was to evaluate whether functional scores at 1-year follow-up in patients who underwent lumbar tubular microdecompression (LTMD) differ before and after the state legislation was enacted.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition, before the pandemic, opioid overdose deaths were on the decline in NC as a result of the state's SUD legislation passed in 2017 (the STOP Act) that targeted opioid prescribing and increasing access to the overdose reversal drug naloxone. 39,40 Given the increasing demand for treatment described by our respondents and the myriad policy changes during COVID, future studies will be needed to understand how these policy changes interact with pre-COVID legislation.…”
Section: Discussionmentioning
confidence: 99%